Regulation of the Vitis vinifera PGIP1 gene encoding a polygalacturonase-inhibiting protein - Joubert, Dirk Albert, 1973- (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD)--University of Stellenbosch, 2004.